PCR Detection of Granulocytic Ehrlichiae in Ixodes ricinus Ticks and Wild Small Mammals in Western Switzerland - Liz, Jorge S. (American Society for Microbiology, 2000)
The presence of granulocytic ehrlichiae was demonstrated by PCR in Ixodes ricinus ticks and wild small mammals in Switzerland in two areas of endemicity for bovine ehrlichiosis. Six ticks (three females and three nymphs) (1.4%) of 417 I. ricinus ticks collected by flagging vegetation contained ehrlichial DNA. A total of 201 small mammals from five species, wood mouse (Apodemus sylvaticus), yellow-necked mouse (Apodemus flavicollis), earth vole (Pitymys subterraneus), bank vole (Clethrionomys glareolus), and common shrew (Sorex araneus), were trapped. The analysis of I. ricinus mammals collected on 116 small mammals showed that nine C. glareolus voles and two A. sylvaticus mice hosted infected tick larvae. In these rodents, granulocytic ehrlichia infection was also detected in blood, spleen, liver, and ear samples. Further examinations of 190 small mammals without ticks or with noninfected ticks showed the presence of ehrlichial DNA in spleen and other tissues from six additional C. glareolus, three A. flavicollis, and one S. araneus mammals. This study suggests that A. sylvaticus, A. flavicollis, S. araneus, and particularly C. glareolus are likely to be natural reservoirs for granulocytic ehrlichiae. Partial 16S rRNA gene sequences of granulocytic ehrlichiae from ticks and rodents showed a high degree of homology (99 to 100%) with granulocytic ehrlichiae isolated from humans. In contrast, groESL heat shock operon sequence analysis showed a strong divergence (approximately 5%) between the sequences in samples derived from rodents and those derived from samples from questing ticks or from other published ehrlichia sequences. Dual infections with granulocytic ehrlichia and Borrelia burgdorferi were found in ticks and small mammals.